2020
DOI: 10.1186/s12888-020-2429-4
|View full text |Cite
|
Sign up to set email alerts
|

Can participatory video reduce mental illness stigma? Results from a Canadian action-research study of feasibility and impact

Abstract: Background: Evidence suggests that stigma against people with mental illness remains high. This demands innovative approaches to reduce stigma. One innovative stigma reduction method is participatory video (PV), whereby marginalized people come together to script, film and produce bottom-up educational videos about shared issues. These videos are then shown to target groups. This paper has two objectives (i) to examine the feasibility of using participatory video with people with severe mental illness (SMI); a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…In general, the PV was seen as an effective learning tool to activate participants, including people with special needs by adult educators, which is consistent with the results of several case studies (Fedeli, 2020;Fedeli, 2019a;2019b;Whitley et al, 2020).…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 86%
See 1 more Smart Citation
“…In general, the PV was seen as an effective learning tool to activate participants, including people with special needs by adult educators, which is consistent with the results of several case studies (Fedeli, 2020;Fedeli, 2019a;2019b;Whitley et al, 2020).…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 86%
“…Unfortunately, there is limited research on this subject in the literature. Whitley et al (2020) researched to examine the feasibility of using PV with people with severe mental illness. According to their study, using PV with people with mental illness is an effective anti-stigma intervention, and the videos and screenings affect viewers positively and could be an effective means of reducing stigma.…”
Section: A Brief Literature On Participatory Videomentioning
confidence: 99%
“…To improve understandability, websites can include summaries of key information and visual aids. The lack of visual materials is problematic, as videos may be an effective means of destigmatizing mental illness [ 44 , 45 ]. As well, women may prefer greater visual aids when learning about postpartum depression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Digital storytelling is a powerful process for co-creation, as it allows marginalized people to script, film, and produce videos of their own stories with support from an experienced facilitator (Whitley et al, 2020). Digital storytelling has been found to be an effective approach to help the storytellers to process their mental health issues (De Vecchi et al, 2016).…”
Section: Co-creation and Stakeholder Engagementmentioning
confidence: 99%
“…However, the current review found no empirical research examining if digital stories can improve the mental health literacy of the viewers, specifically of young people. The recent study by Whitley et al (2020) is the first of its kind to investigate the effect of digital stories created by people with severe mental illness on stigma in viewers, and they found that such digital stories had a positive impact on the viewers' attitudes. Although this study was not included in the current review as the age of the viewers did not meet our inclusion criteria, the results of the study show a great potential of digital stories as an intervention to improve the mental health literacy of the viewers, including young people.…”
Section: Co-creation and Stakeholder Engagementmentioning
confidence: 99%